Pengaruh Working Capital, Sales, Operating Profit dan Cash Profit Terhadap Default Sukuk di Indonesia - Atik Fazalina; Raditya Sukmana (Universitas Airlangga, 2017)
This research aims to determine how four ratios from new altman z-score model affect sukuk default in Indonesia. The case of sukuk default in Indonesia occur by PT Berlian Laju Tanker. These ratios are working capital to total assets, sales to total assets, operating profit to total assets and the cash profit to total assets. Approach used is the logistic regression, as the dependent variable in this research is a dichotomous variable with two categories in the form of default and non-default. The sample used in the period 2007: Q1 to 2015: Q3. The results of this research obtained that the influence of four variables used are the working capital to total assets, sales to total assets, operating profit to total assets and the cash profit to total assets was significant toward sukuk default of Berlian Laju Tanker.